2021
DOI: 10.1111/ropr.12413
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Policy Networks at the Local Level in Germany

Abstract: Research on policy network formation has contributed to an understanding of the patterns of interaction among political actors. Belief homophily, power seeking, and opportunity structures provide explanations studied for specific policy areas. This study tests these established theories in a different environment by asking: What drives policy network formation at the local level? From a review of the literature on policy networks and local politics, the study derives nine hypotheses, which are tested for a Ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 79 publications
(127 reference statements)
0
3
0
1
Order By: Relevance
“…The results showed that the majority of these publications were focused on the education sector (Araujo & Lopes, 2021; Ferrare et al, 2021; Rowe, 2021; Saura, 2021; Schuster et al, 2021; Viseu & Carvalho, 2021). Furthermore, topics, such as climate change (Da Rimini et al, 2021; Howe et al, 2023; Kammerer et al, 2021; Wagner et al, 2021), public housing policy (Akashi, 2021; Raynor & Whitzman, 2021), local politics (Möck, 2021; Seippel & Belbo, 2021), environmental governance (Baulenas et al, 2021; Lutz-Ley et al, 2021), and transnational policy (Crowley-Vigneau et al, 2021; Henriksen & Seabrooke, 2021; Kim, 2021; Saguin & Howlett, 2021) were also discussed.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the majority of these publications were focused on the education sector (Araujo & Lopes, 2021; Ferrare et al, 2021; Rowe, 2021; Saura, 2021; Schuster et al, 2021; Viseu & Carvalho, 2021). Furthermore, topics, such as climate change (Da Rimini et al, 2021; Howe et al, 2023; Kammerer et al, 2021; Wagner et al, 2021), public housing policy (Akashi, 2021; Raynor & Whitzman, 2021), local politics (Möck, 2021; Seippel & Belbo, 2021), environmental governance (Baulenas et al, 2021; Lutz-Ley et al, 2021), and transnational policy (Crowley-Vigneau et al, 2021; Henriksen & Seabrooke, 2021; Kim, 2021; Saguin & Howlett, 2021) were also discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Similarities in city characteristics suggest potential common social problems and shared policy interests (Dye et al 1963). Moreover, local governments that face similar problems and have comparable attributes understand each other better (Carr, LeRoux and Shrestha 2009; Henry 2021; Lubell et al 2017, Möck 2021; Song, Park and Jung 2018). In this sense, diversity in the network may hinder effective information sharing and resource mobilization (Bel and Warner 2016; Feiock 2007), since heterogeneity in city characteristics and preferences creates “… a greater coordination burden than faced by small homogenous networks” (Provan and Milward 2001, 418).…”
Section: Hypothesesmentioning
confidence: 99%
“…Para Bresser y Jones (1998), estos grupos pueden ser identificados como unos concernientes al gobierno (agencias de gobierno y aliados) y otros como grupos meta (organizaciones individuales, actores individuales o colectivos, gubernamentales, de representación etc.). Existen otro tipo de actores como las sedes internacionales y los organismos internacionales o multilaterales (Möck, 2021;Béland y Orenstein, 2013). De igual forma, la conformación inicia por el vínculo o la relación entre actores, posicionándose como un primer paso para la existencia de la red.…”
Section: Características De La Red: Construyendo Un Vínculo Causalunclassified